The politics of Global AIDS : institutionalization of solidarity, exclusion of context - Seckinelgin , Hakan (Springer, 2020)
Contents: Preface -- Chapter 1 Introduction -- Chapter 2 Pathways to the politics of Global AIDS and the meanings of AIDS -- Chapter 3 Institutionalization of Global AIDS and the creation of the Joint United Nations Programme on HIV AIDS (UNAIDS) -- Chapter 4 Civil Society and Solidarity in the politics of Global AIDS -- Chapter 5 Global AIDS and the Politics of Knowledge -- Chapter 6 Evidence-based Policy: Randomized Controlled Trials' Knowledge Claims to AIDS Policy -- Chapter 7 Context Matters! But Why? -- Chapter 8 Conclusion: Emergency, Sustainability and Success.